PENINGKATAN KEAKTIFAN BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN ROLE PLAYING PADA PEMBELAJARAN BAHASA INDONESIA - Ahmad Sigit; Mislan; Nisa Ailia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted due to the low level of learning activeness among fourth-grade students in Indonesian language learning at SDN 114/VII Bukit Kalimau Ulu 1. The study aimed to describe the implementation of the Role Playing learning model and to determine the improvement of students' learning activeness in learning short drama. This research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were 19 fourth-grade students. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The results showed that the implementation of the Role Playing learning model improved students' learning activeness. Observation results increased from 51.51% in the pre-cycle to 72.72% in Cycle I and 89.39% in Cycle II. Questionnaire results also increased from 58.40% in the pre-cycle to 73.63% in Cycle I and 88.75% in Cycle II. Therefore, the Role Playing learning model was proven effective in improving students' learning activeness in Indonesian language learning, particularly in short drama material for fourth-grade students at SDN 114/VII Bukit Kalimau Ulu 1.